Static 3D model of the Rotliegend deposits - case study from natural gas field area, Fore-Sudetic Monocline, Western Poland - Ząbek, Gabriel (Wydawnictwa AGH, 2012)
The »Z« natural gas field is located in the southern part of the Fore-Sudetic Monocline, in the western part of Poland. Rotliegend sandstones, characterized by good reservoir properties are located in the Polish part of the Southern Permian Basin (Gast et al. 2010). The »Z« gas deposit was discovered in 1978.
Geology, Geophysics & Environment
Keywords: Z gas deposit; Petrel software